Stres Kerja pada Perawat di Lembaga Pemasyarakatan - Esra Devi Tarida Lubis; Siti Saidah Nasution; Riswani Tanjung (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to identify the work stress of nurses in Correctional Institutions (LP). The method used is a systematic review by searching articles on the Proquest, Pubmed and ScienceDirect databases with the keywords